Dikotomi Sarana Dan Prasarana Pendidikan Di Indonesia - Marwan, Iis; Gustaman, Randy Fadilah; Gandi, Agus (Cendekia: Jurnal Pendidikan dan Pemberdayaan Masyarakat, 2024)
Abstract. Educational facilities and infrastructure play an important role in achieving an effective learning process. Facilities include equipment and supplies such as tables, chairs and teaching aids, while infrastructure includes supporting facilities such as buildings, laboratories and libraries. The availability of complete educational facilities, such as libraries with diverse book collections and internet access, can increase students' engagement in learning and motivate them to study. The research method used in this study is a literature study, which aims to collect data and information from written sources to build a strong theoretical foundation and strengthen research arguments. Data from BPS and the Ministry of Health show an imbalance in educational facilities and infrastructure between urban and rural areas. In urban areas, 88% of classrooms are in decent condition, while in rural areas only 62%. In addition, 85% of schools in urban areas have internet access, while only 30% in rural areas. Library availability is also much different, with 75% of schools in urban areas having libraries, while in rural areas it is only 45%. Laboratories are available in 60% of urban schools but only 20% in rural areas. In terms of sanitation, 90% of schools in urban areas have proper facilities, while only 50% in rural areas. Various factors such as geography, economy, government policies and cultural aspects contribute to this gap.